2016
DOI: 10.1088/0953-2048/29/12/125006
|View full text |Cite
|
Sign up to set email alerts
|

Modeling tunneling for the unconventional superconducting proximity effect

Abstract: Recently there has been reinvigorated interest in the superconducting proximity effect, driven by predictions of the emergence of Majorana fermions. To help guide this search, we have developed a phenomenological model for the tunneling spectra in anisotropic superconductor-normal metal proximity devices. We combine successful approaches used in s-wave proximity and standard d-wave tunneling to reproduce tunneling spectra in d-wave proximity devices, and clarify the origin of various features. Different variat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
(141 reference statements)
0
5
0
Order By: Relevance
“…Using topological insulators grown on a d-wave superconductor and ARPES the groups of T. Valla and Z. Hasan [143,163] concluded that the proximity effect is prohibited in these structures due to Fermi surface mismatch. Burch's group, based on exfoliated dwave/TI devices, transport experiments [164] and theory [14] showed the opposite. To our knowledge, no other topological insulator in proximity with d-wave superconductors has been studied so far, which might be due to the growth conditions making it difficult to combine both class of materials.…”
Section: Experiments On Topological Insulators and D-wave Superconduc...mentioning
confidence: 99%
“…Using topological insulators grown on a d-wave superconductor and ARPES the groups of T. Valla and Z. Hasan [143,163] concluded that the proximity effect is prohibited in these structures due to Fermi surface mismatch. Burch's group, based on exfoliated dwave/TI devices, transport experiments [164] and theory [14] showed the opposite. To our knowledge, no other topological insulator in proximity with d-wave superconductors has been studied so far, which might be due to the growth conditions making it difficult to combine both class of materials.…”
Section: Experiments On Topological Insulators and D-wave Superconduc...mentioning
confidence: 99%
“…It should be noted that in a real system, one must also account for the evolution of the wavefunctions and potential multiple reflections. Numerical calculations in s-wave [63] and in d-wave [64] proximity junctions confirmthis picture. Thus the induced and reduced gaps produce Andreev features in the dI/dV that are tell-tale signs of the proximity effect [18,19,29,[58][59][60][61][62].…”
Section: Modelmentioning
confidence: 99%
“…The observed features are reproduced by modifying a standard approach to tunneling into d-wave superconductors [30,60,63,64]. Specifically, the differential conductance below T c [dI/dV] S , divided by the normal state conductance [dI/dV] N is given by the half-sphere integration over the solid angle Ω:…”
Section: Modelmentioning
confidence: 99%
“…The momentum parallel to the interface is conserved and therefore, the induced pairing for d-superconductors takes the form given in Eq. ( 11) [34,[43][44][45][46]. Note that for an s-wave parent superconductor where ∆(k) = ∆ s is constant, the above condition, |V | ∆(k), is more restrictive than for a d-wave parent superconductor, where |V | ∆(k) is automatically satisfied for k ∼ 0, unlike the s-wave case.…”
Section: A Derivation Of the Hamiltonianmentioning
confidence: 99%